If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=3/4F+5
We move all terms to the left:
(F)-(3/4F+5)=0
Domain of the equation: 4F+5)!=0We get rid of parentheses
F∈R
F-3/4F-5=0
We multiply all the terms by the denominator
F*4F-5*4F-3=0
Wy multiply elements
4F^2-20F-3=0
a = 4; b = -20; c = -3;
Δ = b2-4ac
Δ = -202-4·4·(-3)
Δ = 448
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{448}=\sqrt{64*7}=\sqrt{64}*\sqrt{7}=8\sqrt{7}$$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-20)-8\sqrt{7}}{2*4}=\frac{20-8\sqrt{7}}{8} $$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-20)+8\sqrt{7}}{2*4}=\frac{20+8\sqrt{7}}{8} $
| 6x+2=2x=1 | | 5(m-17)+1=7(m+5)+1 | | -5+-5x=144 | | (x)=((4-x))/((x-2)) | | r+2/2=9r-237 | | -6a=-3 | | 4y–12=0 | | 35x^2+47x-1=-7 | | 6x-5(1-2x)=-8(1-2x)+3 | | 2(2x-3)-4(3x)=6 | | 3x+7+-1x=5x+1 | | 3(x+13)=8x+4 | | 4*6n=144 | | 6x+3+8=20 | | 7(y-4)-2(y+7)=7-2(4y-5) | | 2/5c+1=c+1/2 | | y+1/3=2y-48 | | 4y-8=5-2y | | 8.70+6.11x=19.91x-7.86 | | -16x^2+40x+12=0 | | 1.47+2.3r=-2.4(r+8.2) | | 4x+3/2=4 | | 82-29(-15a+4)=-34(21a+1) | | x+x+0.37+x+0.37+0.98=10.54 | | d+1/2=5d-121 | | 24-12=2(x-2) | | 2y^+5y-12=0 | | 53+11/6x+1/2x=7/3x+1+4/3x | | -3/5=7/15-x | | 3g-130=10g/9+6 | | |x|-19-1=3 | | 2x-17x=15 |